Effects of drip irrigation on yield, soil fertility and soil enzyme activity of different potato varieties in Northwest China - Zhang, Fan; Chen, Mengru; Fu, Jintao; Zhang, Xiangzhu; Li, Yuan; Xing, Yingying (Frontiers in Plant Science, 2023)
The effects of different irrigation and fertilization on potato yield, soil fertility and soil enzyme activity of different varieties under drip irrigation fertilization mode were studied, which could provide support for selecting the best varieties in Northwest China. Three factors and three levels orthogonal experimental design method, a total of nine treatments. The three irrigation levels were W1 (100% crop evapotranspiration (ETC)), W2 (80% ETC) and W3 (60% ETC). The three fertilization levels were F1 (N-P2O5-K2O, 240-120-300 kg ha−1), F2 (180-90-225 kg ha−1) and F3 (120-60-150 kg ha−1). The three varieties were V1 (Feiuritar), V2 (Longshu7) and V3 (Qingshu 9). The results showed that different irrigation and fertilization had significant effects on potato yield, soil fertility and soil enzyme activity in root zone. The highest yield of T5 (80%ETC, 180-90-225 kg ha−1, Qingshu 9) was 49,222.3 kg ha−1. With the increase of fertilizer application rate, potato yield and soil enzyme activity in root zone increased first and then decreased, but soil electrical conductivity (SEC), soil nitrate-N content (SNNC), soil alkali-hydrolyzable nitrogen content (SAHC), soil available potassium (AK), soil available phosphorus (AP), soil ammonium-N content (SANC) and soil organic matter (SOM) in root zone increased continuously. The yield, soil catalase activity, soil urease activity and soil sucrase activity at W2 were 2.81% and 22.2%, 1.84% and 7.04%, 8.26% and 9.62%, 5.34% and 13.36% higher than those at W1 and W3, respectively. The overall trend of soil water content, soil nutrient content and enzyme activity in root zone was 0–20 cm >20–40 cm >40–60 cm soil layer. There were many soil factors affecting tuber yield, among which soil enzyme activity, pH value and root zone conductivity were the key factors. The results showed that T5 (80%ETC, 180-90-225 kg ha−1, Qingshu 9) was the best treatment to improve soil enzyme activity and yield.